THE QUR’ANIC CONCEPT OF BEAUTY AS ENVIRONMENTAL PEDAGOGY: A TAFSĪR MAWDŪ'Ī STUDY IN INDONESIAN PESANTREN - Taufikin Taufikin; Ahmad Hariyadi (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2026)
Research on student well-being in Islamic educational settings has primarily focused on psychological, spiritual, and instructional dimensions, while the pedagogical role of environmental aesthetics rooted in Qur’anic teachings remains underexplored. Existing studies have rarely examined how the Qur’anic concept of beauty can be translated into an educational framework that supports student well-being in contemporary Islamic boarding schools. This study aims to conceptualize Qur’anic beauty as a form of environmental pedagogy and examine its contribution to student well-being in Indonesian pesantren.This research employed a qualitative integrative design that combined thematic Qur’anic interpretation (tafsīr mawḍū‘ī) based on Tafsīr al-Jalālayn with contextual field research in three Islamic boarding schools. Data were collected through thematic analysis of Qur’anic verses, observations, semi-structured interviews with 22 key informants, and institutional document analysis.The findings reveal that Qur’anic beauty is articulated through concepts such as jamāl, ḥusn, zīnah, sakīnah, mīzān, fiṭrah, and nūr, which are synthesized into six dimensions: visual–aesthetic beauty, moral–social beauty, psychological calmness, harmony and balance, fitrah-based human-centered beauty, and spiritual–illuminative beauty. These dimensions are embedded in physical spaces, social interactions, institutional culture, and spiritual practices within pesantren. Beauty functions not merely as an aesthetic attribute but as a pedagogical mechanism that promotes emotional stability, social security, spiritual resilience, and meaningful learning engagement. This study contributes to Qur’anic and Islamic educational scholarship by developing an environmental pedagogical framework grounded in Qur’anic conceptions of beauty.